THE ACCOUNTING EDUCATION IN LIBYAN UNIVERSITIES AFTER LIBYAN REVOLUTION OF 2011 - Kalifa, Abdarahman M; Triyuwono, Iwan; Djamhuri, Ali (The International Journal of Accounting and Business Society, 2015)
The aim of this paper is to explore the accounting educa- tion in Libyan universities after Libyan revolution of 2011